'Tell me the story is and do not leave out anything'. Social responsibility and ethical practices in the translation of complainants' narratives: the potential for change. (3rd April 2017) - Harding, Sue-Ann; Ralarala, Monwabisi K.
ABSTRACT: A civilian complainant's first encounter with an officer at a local police station in South Africa is an example of an event in which language, translation, narrative, power, law and criminal justice are all interconnected. Statements written by officers during these sessions form the basis of any further legal action and are a critical aspect of the law. In discharging this function, officers act as both intra-lingual and inter-lingual translators. By analysing these (usually discarded) recordings of complainants' narratives, our research enables a comparative textual analysis of the oral isiXhosa original and written English statement. Drawing on social narrative theory, this paper interrogates these translations and translation practices, noting omissions of events, actors and descriptions which result in a significant reconfiguration of the original narrative. We argue that the step of inter-lingual translation should be omitted from the statement-taking process. Raising awareness of the manipulations inherent in these practices can help develop an ethical approach to police training that promotes and enables a culture of institutional responsibility, ethical translation and social and criminal justice, even in difficult encounters.